Avoiding the road to nowhere: insights on scaling up and sustaining digital health - LeFevre, Amnesty; Chamberlain, Sara; Singh, Neha S.; Scott, Kerry; Menon, Purnima; Barron, Peter; Ved, Rajani; George, Asha (John Wiley & Sons, 2021)
Digital health solutions offer tremendous potential to enhance the reach and quality of health services and population-level outcomes in low- and middle-income countries (LMICs). While the number of programs reaching scale increases yearly, the long-term sustainability for most remains uncertain. In this article, as researchers and implementors, we draw on experiences of designing, implementing and evaluating digital health solutions at scale in Africa and Asia, and provide examples from India and South Africa to illustrate ten considerations to support scale and sustainability of digital health solutions in LMICs. Given the investments being made in digital health solutions and the urgent concurrent needs to strengthen health systems to ensure their responsiveness to marginalized populations in LMICs, we cannot afford to go down roads that ‘lead to nowhere’. These ten considerations focus on drivers of equity and innovation, the foundations for a digital health ecosystem, and the elements for systems integration. We urge technology enthusiasts to consider these issues before and during the roll-out of large-scale digital health initiatives to navigate the complexities of achieving scale and enabling sustainability.